Examination timetabling using harmony search algorithm - Zainal Abidin, Muhamad Fauzi (2015)
The examination timetabling problem concerns with the process of assigning exam entities to the particular slots and rooms in a timetable. The aim is to fulfil the hard constraints as well as the soft constraints to the highest grade possible in order to construct an optimum timetable. In this project, the Harmony Search Algorithm (HSA) has been applied to develop the examination timetable for Kolej Profesional MARA. The HSA consist of five steps, which are initialize the HSA parameters, initialize the Harmony Memory (HM), improvise new solutions, update the HM and achieve the termination criteria. The results stated in this research has been showed that the proposed examination timetable system capable to construct the timetable in fewer time compare with the current approach.